Representation of the Poor’s Plight in Vaikom’s “Birthday”: A Social Realistic Approach - Bhatta, Laxman (Bon Voyage, 2019)
This paper explores the plight of a poor student who doesn’t have a penny to celebrate his birthday. “Janmadinaa” (Birthday) is a story originally written in Malayalam, narrated from the autobiographical perspective. Vaikom Muhammad Basheer, the narrator, makes the readers observe pathetically different encounters with his friends and neighbours. His friends and neighbours look at him with strange gaze and deny lending him even an ‘anna’ (rupee) to have a morsel of food and a cup of tea on his birthday. Vaikom has varieties of groups of characters: the poor, the students, and the helpless and rich people through the perspective of social realism. Social realism by George Lucks describes socio-economic reality that rejects the deterministic relationship between the reality and its underlying meaning. Largely this article deploys Lucks’s concept to explicate Vaikom’s story and reflects upon the issue of pretty misery of the protagonist. The story encapsulates an optimistic remark that the poor people always remain active and raise voice against the socio-economical domination from the elites.